Psychological mindedness as a mediator in the relationship between dysfunctional coping styles and depressive symptoms in caregivers of children with autism spectrum disorder - Pang, Nicholas Tze Ping; Ruziana Masiran; Kit‐Aun Tan; Aminah Kassim (2020)
Purpose Psychological mindedness (PM) can partly explain depressive symptoms in caregivers of autism spectrum disorder (ASD). This cross‐sectional study examines PM in mediating the relationship between dysfunctional coping styles and depressive symptoms. Design and Methods One hundred fifty‐five adult ASD caregivers completed the Malay version of Brief COPE, the Patient Health Questionnaire‐9, and the Balanced Index of PM. Findings Direct paths between dysfunctional coping style and depressive symptoms, between insight and depressive symptoms, and between dysfunctional coping style and all PM variables (insight and interest) were obtained. Multiple regression analyses revealed that insight, but not interest, significantly mediates the relationship between dysfunctional coping and depressive symptoms. Practical Implications PM can be enhanced via psychological interventions.